A mixed-valence metallogrid [CoIII2CoII2] with an unusual electronic structure and single-ion-magnet characterization. Issue 15 (31st March 2017) - Huang, Wei; Pan, Feifei; Wang, Zhenxing; Bai, Yan; Feng, Xuejun; Gu, Jiande; Ouyang, Zhong-Wen; Wu, Dayu
Abstract : Magnetically isolated weakly coordinated cobalt(ii ) ions with an unusual electronic structure in a mixed-valence metallogrid show field-induced slow magnetization relaxation. Abstract : The reaction of the multisite coordination ligand (H 2 L ) with Co(Ac)2 ·4H2 O in the absence of any base affords a homometallic tetranuclear mixed-valence complex, [Co4 (L)4 (CH3 CO2 )2 (CH3 OH)2 ]·Et2 O (1 ). This mixed-valence metallogrid [Co4 (L)4 (CH3 CO2 )2 (CH3 OH)2 ]·Et2 O (1 ) has been theoretically and experimentally analyzed to assign the valence and spin state in the form of trans -[CoIIIls–CoIIhs–CoIIIls–CoIIhs]. HF-EPR reveals the presence of axial anisotropy ( D = −34.4 cm −1 ) with a significant transverse component ( E = 9.5 cm −1 ) in the local high spin cobalt centers. Slow magnetic relaxation effects were observed in the presence of a dc field, demonstrating field-induced single ion magnetic behavior, which is associated with the unusual electronic structure of Co(ii ) within the metallogrid.